Penerapan Layanan Konseling Pada Siswa Yang Melanggar Tata Tertib Sekolah Di Madrasah Aliyah Darunnah Lumajang - Moh. Muafi Bin Thohir (Institut Agama Islam Syarifuddin Lumajang, 2019)
The background problem of this study is the existence of violations of the rules of conduct committed by students in Madrasah Aliyah Darunnajah Lumajang school, on the other hand, guidance and counseling services in schools are entrusted to BK teachers to help and guide students to better and prevent students from doing more violation. This research is focused on the application of counseling services to students who violate school rules. While the objectives to be achieved in this study were to determine the Application of Counseling Services to Students Who Violated School Rules in Madrasah Aliyah Darunnajah Lumajang. The research method used in this research is descriptive qualitative research. The data collection method used is the method of observation, interview methods and documentation methods. The results of this study are that after getting counseling from counseling teachers, students no longer repeat violations of school rules, whether they are minor, moderate, or severe violations. The results of the guidance and counseling applied by the BK teacher is that students become better at obeying school rules and regulations. The services used by BK teachers are individual counseling services, group counseling, and information services. It is expected that in implementing the guidance and counseling service by the BK teacher, students can obey the school rules set by the school without being forced to and with self-awareness. Key words: Counseling, Rules of Conduct, Violations